PERANCANGAN MAJALAH SIMANIS EDISI PANDUAN PEMELIHARAAN DAN PERAWATAN KUCING - ASMA DEWI, Ir. Drs. Heldi, M.Si., Ph.D., Dra. Lisa widiarti, M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Not all of the cat owners know how to treat and take care of the cats correctly. It might cause the cats  become sleazy. Meanwhile, the cat magazines with the edition how to treat and take care of the cats are still rarely found in Indonesia. The purpose of "majalah simanis" in the guidance to treat and take care of the cats edition is to give an informative and communicative information so that the information can be understood easily.This design methodology through the qualitative descriptive method. This means that data collected is not a number, but data derived from interviews, field notes, documentation, and official documents.Magazine is designed by using the theory of visual communication design, media, books, animal  magazines, colors, photography, layouts, and typography. The data were collected by using  observation method, interview and documentation method. Method of data analysis by using the  technique of 5W+1H ( what, when, where, why, who + how).The design of the magazine as the main media is also supported by several media such as posters,  x-banners, bookmarks, cat eating places, tota bags, small towels and medicine boxes that are useful  as main media supporters and as promotional media.Key Words : Maganize, Guidance, Breeding, Treatment, Cats